Characterization of imogolite-type nanoparticles in Podzols: morphology and association with iron - Tove Florén; Manuel Bartolomé Díaz; Geert Cornelis; Stephen Hillier; Jon Petter Gustafsson (Geoderma)
Imogolite-type nanoparticles (ITN) are among the most extensively studied particles present in the Bs horizons of Podzols, as they are strongly associated with the adsorption processes of different anions in soils, including phosphate. The aim of this study was to assess the properties of ITN in soil, in order to increase the current knowledge of ITN regarding adsorption models. ITN were isolated from the B horizons of three Swedish Podzols and characterised in terms of size distribution, morphology, elemental composition, and association with iron. Appreciable amounts of ITN were found in two of the three soil samples studied, reaching up to 14 % ITN by mass if all oxalate-extractable Si is assigned to ITN. Furthermore, substantial amounts of Fe were also present in the selected soil samples. Proto-imogolite (PIM) was the predominant form of ITN, suggesting that tubular imogolite have a lower contribution for ion adsorption reactions in Podzols. Three types of PIM morphology were identified: structureless amorphous clusters, fragmented nanotubes, and globular aggregates. The studied PIM, which exhibited a particle size around 50 nm, contained up to 19 % Fe, while no detectable amounts of Fe were found in tubular imogolite. Regarding PIM, Fe atoms were evenly distributed in the structure, providing evidence for the presence of a substituted and/or surface-adsorbed Fe phase, rather than large ferrihydrite clusters. The present study provides novel insights into the properties of ITN and its association with Fe, which will aid in the development of models predicting the fate of oxyanions in Podzols and other ITN-containing soils.